Песни южных удмуртов - Бойкова Елена Борисовна (Удмуртский фольклор, 1992)
Экземпляры: (20180706) / Инвентарный номер: 31003 / Цена: 120.00 / Сис.шифр: 82.3(2) / Авт.знак: Б 77 / ГРНТИ: 17 / ББК: 82.3(2Рос=Удм).06